Analisis Komparatif Berdasarkan Rasio Profitabilitas Pada PT Garuda Indonesia Tbk dan PT AirAsia Tbk Indonesia Pada Tahun 2020 – 2024 - Nadya Khairiah; Marsa Anjeni; Sylvania Nadisah (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
The aviation industry is one of the transportation sectors that is important in increasing the mobility and economy of a country. PT Garuda Indonesia Tbk and PT AirAsia Indonesia are two industries engaged in aviation as a diverse market segmentation service. The growth of the aviation industry in Indonesia has been negatively impacted by Covid-19, which has resulted in a drastic decline in passenger flow from national cargo from 2020 to 2021, causing both airlines to experience a significant decline in profits and revenues during that period. Both airlines must have the ability to meet operational costs and maintain their financial performance. This study aims to try to compare the comparative analysis of PT Garuda Indonesia Tbk and PT AirAsia Indonesia Tbk using the Profitability Ratio with data that can be taken from the Indonesian Stock Exchange with financial reports for the 2020-2024 period. This study uses a quantitative description method with a focus on calculating financial ratios to indicate overstatement of profits for each airline. The results of the study show that there are differences in different financial reporting patterns. Based on the analysis with the profitability ratio at PT Garuda Indonesia has a very high and unrealistic figure, this can potentially overstate profits or errors in its financial statements, while PT AirAsia Indonesia has a more stable and realistic figure. This can indicate that PT AirAsia is more conservative in financial reporting and does not take aggressive actions to beautify its financial statements.